La obra (in)completa de Alejandra Pizarnik: un acercamiento a su obra inédita a partir de Otoño o los de arriba - Hurtado Tarazona, Alejandra (2015)
Pizarnik is a writer whose work is highly interesting from the editorial point of view, for two particular situations. First, the published work is identified as “complete” when there is no complete edition of this author, because it bears the burden of censorship. Second, this gap causes the necessity of going to Princeton, where is the “original” work of Pizarnik in a more complete version. This paper tries to explore these points, starting from the experience of editing the unpublished work Otoño o los de arriba.